Development of Food Ordering Application in School Canteen - Wong, Chin Rong; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2022)
The Canteen Ordering Application is a mobile-based application powered by Android which act as a new food ordering system instead of ordering food by face to face in secondary school. The aim of developing this mobile application is to solve the problem of students in ordering food manually during Covid-19 where students can register a new account and log in into Canteen Ordering Application to order food, while food seller in secondary school to edit food and beverages for students to take order. Agile methodology phases like envision, speculate, explore, adapt and close are used along this study. The development of this mobile application will lead students to reduce close contact between each of them and save a lot of time when they queue to purchase food and beverages in school canteen. Canteen Ordering Application is an opportunity to reform a school canteen system in the future, online payment method like PayPal is suggested for future work to make this mobile-based application getting stronger.